2020
DOI: 10.5093/pi2019a16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fiction on the Well-Being of Older Adults: A Longitudinal RCT Intervention Study Using Audiobooks

Abstract: A novel takes you somewhere and asks you to look through the eyes of another person, to live another life." (Barbara Kingsolver, 2010). Fiction allows people to enter simulated worlds created from an author's imagination and, by doing so, is proposed to have benefits for cognition and emotion (Koopman & Hakemulder, 2015; Mar & Oatley, 2008; Oatley, 2016). A growing body of research has examined the psychological benefits of fiction, particularly for socio-cognitive and interpersonal processes, but has yet to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Such prevention or intervention could be applied in a low-cost and pleasurable way (e.g., through engagement with fiction). Previous research on cognitive bibliotherapy (therapeutic exposure to verbal art) has suggested a beneficial, long-term effect on mild to moderate depression (see also G. Poerio & Totterdell, 2020;N. M. Smith, Floyd, Scogin, & Jamison, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Such prevention or intervention could be applied in a low-cost and pleasurable way (e.g., through engagement with fiction). Previous research on cognitive bibliotherapy (therapeutic exposure to verbal art) has suggested a beneficial, long-term effect on mild to moderate depression (see also G. Poerio & Totterdell, 2020;N. M. Smith, Floyd, Scogin, & Jamison, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Reading aloud with a young child may be one experience that elicits positive emotional changes. Research shows that reading literature (even alone) can be a positive experience for the reader (Poerio and Totterdell, 2020) and that individuals who frequently read for pleasure are less stressed, depressed, and lonely (Rane-Szostak and Herth, 1995). Poerio and Totterdell (2020) found that listening to audiobooks had the potential to increase an individual's sense of well-being for up to two weeks.…”
Section: Emotional Experiences In Adult Readersmentioning
confidence: 99%
“…Research shows that reading literature (even alone) can be a positive experience for the reader (Poerio and Totterdell, 2020) and that individuals who frequently read for pleasure are less stressed, depressed, and lonely (Rane-Szostak and Herth, 1995). Poerio and Totterdell (2020) found that listening to audiobooks had the potential to increase an individual's sense of well-being for up to two weeks. Researchers concluded that books alone were not the sole factor that affected readers' emotions, but the interactive experience an adult reader had with a story and how engaged they were determined their sense of well-being.…”
Section: Emotional Experiences In Adult Readersmentioning
confidence: 99%
“…A similar study used qur'anic therapy to increase religious coping of hemodialysis patients [15] Since 2002 and improve the mental health and well-being of psychology of lesbian prisoners [16], [17]. Interventions using bibliotherapy through guided reading with therapeutic results in mind become evidence that bibliotherapy can be used to enhance therapy [18], promote good mental and emotional health [19], reduce anxiety and sadness [20], can help identify spiritual needs [21], create a new frame of perception of the situation at hand through fiction and non-fiction reading, thereby encouraging new meanings of life [22].…”
Section: Introductionmentioning
confidence: 99%